EU-Russia Rivalry in the Balkans: Linkage, Leverage and Competition (the Case of Serbia) - Galina A. Nelaeva; Andrey V. Semenov (Romanian Journal of European Affairs)
The article seeks to examine Serbia’s EU integration process in the context of EU-Russia relations in the Western Balkans. Serbia’s path to the EU has been long and problematic, with Serbia recovering from economic turmoil, difficulties in postconflict reconstruction, the destructive floods of 2014, the refugee crisis of 2015, and strained relations with its Balkan neighbours. By applying Levitsky and Way’s theoretical framework that stresses the importance of an external actor in the democratization process (the importance of leverage and linkage vis-à-vis the democratizing state) and the analysis of linkages/leverage with counter-hegemonic states, we argue that in examining competing linkages/leverages, we must acknowledge the importance of the interplay between powerful actors as well. The events of 2014, which have led to a dramatic rift in EU-Russia relations, offered Serbia an opportunity to exit the “grey zone”, as defined by Thomas Carothers, as well as gave the EU the chance to deepen its influence in the Western Balkans.